Dynamical Properties of Scaled Atomic Wehrl Entropy of Multiphoton JCM in the Presence of Atomic Damping - S. Abdel-Khalek; M. S. Almalki; E. Edfawy (Advances in Condensed Matter Physics)
We study the dynamics of the atomic inversion, scaled atomic Wehrl entropy, and marginal atomic Q-function for a single two-level atom interacting with a one-mode cavity field taking in the presence of atomic damping. We obtain the exact solution of the master equation in the interaction picture using specific initial conditions. We examine the effects of atomic damping parameter and number of multiphoton transition on the scaled atomic Wehrl entropy, atomic Q-function, and their marginal distribution. We observe an interesting monotonic relation between the different physical quantities in the case of different values of the number of photon transition during the time evolution.